Alexander Heinemann. Der Gott des Gelages. Dionysos, Satyrn und Mänaden auf attischem Trinkegeschirr des 5. Jahrhunderts v. Chr. - Rodríguez Pérez, Diana (Journal of Greek Archaeology, 2017)
Heinemann’s lavishly illustrated book aims first and foremost to study the images of Dionysos and his cortège on symposium ware during the 5th century BC in their social and ritual contexts. The rationale behind the research is the belief that the decoration deployed on figured pottery is not arbitrary but is intimately and meaningfully intertwined with the use of the vase. Furthermore, the meanings of such imagery are not a prioristic but need to be retrieved by the viewer every time s/he interacts with the object, in an everlasting ‘battle’ between object and subject. Retrieving the potential resonance of such iconography to a given viewer requires in turn an examination of the communication processes—i.e. rituals, plays, etc.—in which the symposium ware is inserted and the particular needs it helped fulfill, which are, unfortunately, lost to us.